Analysis of Factors Affecting Individual Taxpayer Compliance in the City of Bandung by Considering Risk Preference as a Moderating Variable - Zakiah Annisha; Dyah Purnamasari (Publikasi Indonesia, 2025)
Individual Taxpayer Compliance (Wajib Pajak Orang Pribadi - WPOP) is a crucial element in optimizing state revenue from the tax sector. This research aims to analyze the effects of tax amnesty, tax rates, and Machiavellian traits on individual taxpayer compliance in the city of Bandung, as well as to evaluate the role of risk preference as a moderating variable. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, involving 100 individual taxpayers registered at the Primary Tax Office (KPP Pratama) Bandung. The analysis results indicate that tax amnesty and tax rates have a significant positive effect on taxpayer compliance. Conversely, Machiavellian traits have a significant negative effect. Risk preference does not moderate the relationship between tax amnesty and compliance, nor between Machiavellian traits and compliance. However, risk preference was found to moderate the relationship between tax rates and compliance, where taxpayers with a tendency to avoid risk are more compliant with fair changes in tax rates compared to those with high risk tolerance. This research contributes theoretically by integrating psychological and fiscal factors in explaining tax compliance. The practical implication is that policymakers should consider taxpayer behavioral characteristics when designing policies that encourage sustainable voluntary compliance.